Tularemia as a waterborne disease: a review - Aurélie Hennebique; Sandrine Boisset; Max Maurin (Emerging Microbes and Infections)
Francisella tularensis is a Gram-negative, intracellular bacterium causing the zoonosis tularemia. This highly infectious microorganism is considered a potential biological threat agent. Humans are usually infected through direct contact with the animal reservoir and tick bites. However, tularemia cases also occur after contact with a contaminated hydro-telluric environment. Water-borne tularemia outbreaks and sporadic cases have occurred worldwide in the last decades, with specific clinical and epidemiological traits. These infections represent a major public health and military challenge. Human contaminations have occurred through consumption or use of F. tularensis-contaminated water, and various aquatic activities such as swimming, canyoning and fishing. In addition, in Sweden and Finland, mosquitoes are primary vectors of tularemia due to infection of mosquito larvae in contaminated aquatic environments. The mechanisms of F. tularensis survival in water may include the formation of biofilms, interactions with free-living amoebae, and the transition to a ‘viable but nonculturable' state, but the relative contribution of these possible mechanisms remains unknown. Many new aquatic species of Francisella have been characterized in recent years. F. tularensis likely shares with these species an ability of long-term survival in the aquatic environment, which has to be considered in terms of tularemia surveillance and control.